Salvage chemotherapy and autologous stem cell transplantation for peripheral T-cell lymphoma: a subset analysis of the Canadian Cancer Trials Group LY.12 randomized phase 3 study. Issue 10 (3rd October 2017) - Skamene, Tanya; Crump, Michael; Savage, Kerry J.; Reiman, Tony; Kuruvilla, John; Good, David; LeBrun, David; Meyer, Ralph M.; Sehn, Laurie H.; Soulières, Denis; Stakiw, Julie; Laferriere, Nicole; et al.
Abstract: Peripheral T-cell lymphoma (PTCL) is a rare, heterogeneous malignancy. Of the 619 patients with relapsed and refractory (R/R) aggressive lymphoma enrolled in the Canadian Cancer Trials Group LY.12 phase 3 trial, 59 (9.5%) had PTCL. Among these, 81% had advanced stage disease, 41% had an International Prognostic Score ≥3, and 41% were refractory to primary therapy. Within the PTCL cohort, the overall response rate after two cycles of salvage chemotherapy was 36%; no difference was observed between dexamethasone, cytarabine, cisplatin (10/30, 33%), and gemcitabine, cisplatin, dexamethasone (11/29, 38%) therapy. At one year, event-free survival (EFS) was 16% and overall survival (OS) was 28%. For PTCL patients, who received autologous stem cell transplant, two-year EFS and OS were 21% and 42%, respectively. Patients with PTCL had inferior OS (HR 0.49, p  < .0001) and EFS (HR 0.53, p  < .0001) compared to B-cell lymphoma. Outcomes for patients with R/R PTCL are poor with currently available therapies.